Helicobacter Pylori: a comprehensive review for primary care providers - Nelson Alfred; Bi Yan; Harris Dana (Sciendo, 2021)
Helicobacter pylori is the most prevalent bacteria infecting humans resulting in a variety of gastrointestinal and extra gastrointestinal complications. Although most of the infected adults are asymptomatic, the prevalence varies in different parts of the world it is higher in Eastern and Southern Europe. Eradication of Helicobacter pylori is necessary to prevent precancerous conditions like gastric atrophy, gastric intestinal metaplasia and gastric dysplasia. This comprehensive review addresses briefly on: whom and how to test and treat including recommended first line therapies, salvage therapies, testing for eradication and strategy to be used in primary care clinics.